A comparative study of hysteresis current controller and PI controller in grid-connected inverter - Christopher Ngadi, Anak Julius; Lailatul Niza, Muhammad; Hamdan, Daniyal; Norazila, Jaalam; Nor Rul Hasma, Abdullah; Suliana, Ab Ghani (The World Academy of Research in Science and Engineering, 2019)
The use of renewable energy sources is highly demand in electricity market nowadays. The integration of renewable energy sources with utility grid has becoming a challenging task in power system as it arises several control issues such as grid stability, power quality control, loads sharing and others. This paper presents current control methods namely Hysteresis controller and Proportional-Integral controller used to interface single-phase grid connected inverter with nonlinear load. The impact of nonlinear load on grid current is analysed by measuring the performance of total current harmonics distortion (THDi) level in MATLABTM Simulink software environment.